Variation in Exhaled Acetone and Other Ketones in Patients Undergoing Bariatric Surgery: a Prospective Cross-sectional Study - Boshier, Piers R; Fehervari, Matyas; Markar, Sheraz R; Purkayastha, Sanjay; Spanel, Patrik; Smith, David; Hanna, George B (Obesity surgery, 2018)
BACKGROUND: Dietary restriction together with alteration of the gastrointestinal tract results in major metabolic changes and significant weight loss in patients undergoing bariatric surgery. Current methods of measuring these changes are often inaccurate and lack a molecular basis. The objective of this study was to determine the role of exhaled ketones as non-invasive markers of nutritional status in patients undergoing surgical treatment of obesity. METHODS: Patients at different stages of treatment for obesity were recruited to this single-centre cross-sectional study. The sample time points were as follows: (i) at the time of initial attendance prior to dietary or surgical interventions, (ii) on the day of surgery following a low carbohydrate diet, and (iii) > 3 months after either Roux-en-Y gastric bypass or sleeve gastrectomy. The concentrations of ketones within breath samples were analysed by selected ion flow tube mass spectrometry. RESULTS: Forty patients were recruited into each of the three study groups. Exhaled acetone concentrations increased significantly following pre-operative diet (1396 ppb) and bariatric surgery (1693 ppb) compared to the start of treatment (410 ppb, P < 0.0001). In comparison, concentrations of heptanone (6.5 vs. 4.1 vs. 1.4 ppb, P = 0.021) and octanone (3.0 vs. 1.4 vs. 0.7 ppb, P = 0.021) decreased significantly after dieting and surgical intervention. Exhaled acetone (ρ - 0.264, P = 0.005) and octanone (ρ 0.215, P = 0.022) concentrations were observed to correlate with excess body weight at the time of sampling. Acetone and octanone also correlated with neutrophil and triglyceride levels (P < 0.05). CONCLUSION: Findings confirm breath ketones, particularly acetone, to be a potentially clinically useful method of non-invasive nutritional assessment in obese patients.
Keywords: Cross-Sectional Studies; dieta; Weight Loss; Nutritional Status; Gastrectomy; Obesity; Low calorie diet; Nutrition; Middle Aged; mužské pohlaví; gastrektomie; průřezové studie; Adult; Prospective Studies; žaludeční bypass; Exhaled breath; bariatrická chirurgie; aceton; Gastric Bypass; Ketones; ženské pohlaví; Humans; prospektivní studie; dechové testy; Breath Tests; Acetone; biologické markery; hmotnostní úbytek; ketony; lidé středního věku; obezita; Bariatric Surgery; Diet; dospělí; Biomarkers; nutriční stav; Female; Obesity, Morbid; Bariatric surgery; lidé; Male; morbidní obezita